1) В В
2) А Г
3) В В
4) ГВБ АВГ
5) 2/3*[sqrt(3*6-2)-sqrt(3*2-2)]=2/3*(4-2)=4/3, -2/3*[sqrt(4-3*1)-sqrt(4-3*0)]=-2/3(1-2)=2/3
6)
7)
1) В В
2) А Г
3) В В
4) ГВБ АВГ
5) 2/3*[sqrt(3*6-2)-sqrt(3*2-2)]=2/3*(4-2)=4/3, -2/3*[sqrt(4-3*1)-sqrt(4-3*0)]=-2/3(1-2)=2/3
6)![\int\limits_1^4((4-x)-(4x-x^2))\,dx=\int\limits_1^4(x^2-5x+4)\,dx=\\=(\frac {x^3}3-\frac{5x^2}2+4x)_1^4=\frac{63}3-\frac{75}2+12=-\frac92](/tpl/images/0076/3172/8409a.png)
7)![\int_1^2(x^{-3}-e^{-x})\,dx=(\frac{x^{-2}}2+e^{-x})_1^2=\dots](/tpl/images/0076/3172/471d6.png)